Alkoxycarbonyl elimination of 3-O-substituted glucose and fructose by heat treatment under neutral pH. (October 2020) - Chiku, Kazuhiro; Tsukasaki, Riku; Teshima, Yu; Yoshida, Mitsuru; Aramasa, Hiroki; Nihira, Takanori; Nakai, Hiroyuki; Ono, Hiroshi; Kitaoka, Motomitsu
Abstract: 3- O -Substituted reducing aldoses are commonly unstable under heat treatment at neutral and alkaline pH. In this study, to evaluate the decomposition products, nigerose (3- O -α-d -glucopyranosyl-d -glucose) and 3- O -methyl glucose were heated at 90 °C in 100 mM sodium phosphate buffer (pH 7.5). Decomposition via β-elimination was observed that formed a mixture of 3-deoxy- arabino -hexonic acid and 3-deoxy- ribo -hexonic acid; upon further acid treatment, it was converted to their γ -lactones. Similarly, turanose (3- O -α-d -glucopyranosyl-d -fructose), a ketose isomer of nigerose, decomposed more rapidly than nigerose under the same conditions, forming the same products. These findings indicate that 3- O -substituted reducing glucose and fructose decompose via the same 1, 2-enediol intermediate. The alkoxycarbonyl elimination of 3- O -substituted reducing glucose and fructose occurs readily if an O -glycosidic bond is located on the carbon adjacent to the 1, 2-enediol intermediate. Following these experiments, we proposed a kinetic model for the3- decomposition of nigerose and turanose by heat treatment under neutral pH conditions. The proposed model showed a good fit with the experimental data collected in this study. The rate constant of the decomposition for nigerose was (1.2 ± 0.1) × 10 −4 s −1, whereas that for turanose [(2.6 ± 0.2) × 10 −4 s −1 ] was about 2.2 times higher. Graphical abstract: Image 1 Highlights: Nigerose and turanose are unstable against heat treatment under neutral pH. The decomposition by heating results in formation of 3-deoxy-hexonic acids. γ-Lactones are generated by acid treatment of 3-deoxy-hexonic acids. The elimination occurs on the carbon adjacent to the 1, 2-enediol intermediate.